Characterization of minerals, metals, and materials 2013 : proceedings of a symposium sponsored by the Materials Characterization Committee of the Extraction and Processing Division of TMS (The Minerals, Metals & Materials Society) ; held during the TMS Annual Meeting & Exhibition, San Antonio, Texas, USA, March 3-7, 2013 - Hwang, Jiann-Yang (Wiley, 2013)
"This collection of proceedings from one of the most popular TMS symposia explores the current progress in the characterization of materials. Addressing technologies, applications, and innovative research, these papers cover definations of ferrous and nonferrous metals and alloys, minerals, advanced and soft materials, and inorganic materials. Extraction and environmental applications, as well as surface, joint, and processing of metals. This is a valuable reference for scientists and engineers working with materials in the minerals, metals, and materials industry."--